2018
DOI: 10.20937/rica.2018.34.01.05
|View full text |Cite
|
Sign up to set email alerts
|

SEASONAL LEVELS OF HEAVY METALS IN SOFT TISSUE AND MUSCLE OF THE PEN SHELL Atrina maura (SOWERBY, 1835) (BIVALVIA: PINNIDAE) FROM A FARM IN THE SOUTHEASTERN COAST OF THE GULF OF CALIFORNIA, MEXICO

Abstract: The pen shell (Atrina maura) is a filter-feeder bivalve that may accumulate metals in its body. The objective of this study was to determine seasonal concentrations of copper (Cu), chromium (Cr), cadmium (Cd), nickel (Ni), lead (Pb), arsenic (As), zinc (Zn), and mercury (Hg) in soft tissue and muscle of A. maura cultivated in a farm located in the southeastern coast of the Gulf of California from summer 2011 to summer 2012. Except for Cu, the higher metal concentrations were found during the dry season (winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…For instance, Frías-Espericueta et al ( 2008) obtained higher Cu (21-73.2 µg/g dw) and Cd (1.8-7.2 µg/g dw) levels, but lower Pb (2.6-8.7 µg/g dw) burdens in a wild bank of the pleasure oyster (Crassostrea corteziensis) from the Altata bay. The Zn (1-1.66 µg/g dw), Cr (0.4-1 µg/g dw), Ni (0.33-2.3 µg/g dw), Pb (0.66-2 µg/g dw), and As (0.2-0.57 µg/g dw) concentrations reported by Góngora-Gómez et al (2018) in the muscle of the pen shell (Atrina maura) cultivated at a farm located between the two sample sites were lower than the levels we obtained for Zn (2.44-5.16 µg/g dw), Cr (3.51-9.76 µg/g dw), Ni (2.49-8.55 µg/g dw), Pb (6.68-14.45 µg/g dw), and As (0.4-1.82 µg/g dw). Muñoz-Sevilla et al ( 2017) registered variations of Cu (10.2-26.6 µg/g dw), Cd (0.8-3.8 µg/g dw), Pb (1.3-3.6 µg/g dw), Zn (57.2-219.4 µg/g dw), and Hg (0.02-0.11 µg/g dw) in Pacific oysters (C. gigas) cultivated near the Agiabampo bay.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For instance, Frías-Espericueta et al ( 2008) obtained higher Cu (21-73.2 µg/g dw) and Cd (1.8-7.2 µg/g dw) levels, but lower Pb (2.6-8.7 µg/g dw) burdens in a wild bank of the pleasure oyster (Crassostrea corteziensis) from the Altata bay. The Zn (1-1.66 µg/g dw), Cr (0.4-1 µg/g dw), Ni (0.33-2.3 µg/g dw), Pb (0.66-2 µg/g dw), and As (0.2-0.57 µg/g dw) concentrations reported by Góngora-Gómez et al (2018) in the muscle of the pen shell (Atrina maura) cultivated at a farm located between the two sample sites were lower than the levels we obtained for Zn (2.44-5.16 µg/g dw), Cr (3.51-9.76 µg/g dw), Ni (2.49-8.55 µg/g dw), Pb (6.68-14.45 µg/g dw), and As (0.4-1.82 µg/g dw). Muñoz-Sevilla et al ( 2017) registered variations of Cu (10.2-26.6 µg/g dw), Cd (0.8-3.8 µg/g dw), Pb (1.3-3.6 µg/g dw), Zn (57.2-219.4 µg/g dw), and Hg (0.02-0.11 µg/g dw) in Pacific oysters (C. gigas) cultivated near the Agiabampo bay.…”
Section: Discussionmentioning
confidence: 90%
“…To analyze the metal burdens, the clam soft tissue samples (1-1.5 g dw) were digested with 3 ml of 70 % NHO 3 and 0.5 ml of 30 % H 2 O 2 using a microwave digestor (Parr Physica Multiwave Six Place) at 300 W for 5 min, then at 600 W for 10 min, which proved to be satisfactory for an adequate digestion of samples. Digestions were performed and stored until metal analysis as described by Góngora-Gómez et al (2018).…”
Section: Trace Metal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Such seasonal fluctuations were largely correlated with seasonal changes in flesh weight during the development of gonatic tissues (Otchere 2003;Bustamante and Miramand 2005). A similar increase of cadmium levels during the dry season was observed by Góngora-Gómez et al (2018). Contrary to these results, Bjerregaard and Depledge (1994) concluded that cadmium uptake and bioaccumulation in crustaceans and mollusks are higher at low salinities during the rainy season.…”
Section: Discussionmentioning
confidence: 92%
“…The minimum and maximum Cd as μg/g detected in C. gasar tissue were 0.16 μg/g in ST2 (also ST4) and 6.08 μg/g in ST6. Some of Cd levels in bivalves reported in the literature were in the range of 0.6 to 1.25 mg/kg ww with an average value of 16.6 mg/kg ww in Boulay Island 15 , 0.6-1.03 μg/g ww in C. gasar from a lagoon in Togo 16 , 1.93-62.62 μg/g dw 27 , 23-33 dw 28 , 0.001-0.13 mg/g dw 11 . C. gasar inhabiting in NIGER Delta was thus more contaminated with Cd than those of the Milliardaires Bay.…”
Section: Results and Discusionmentioning
confidence: 99%